(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The western theonym Durbedico is a denominative adjective derived from the place name also testified in Callaecia, Durbede (ablative). There is an exact parallel of the place name Durbede in Durbeta / Dorbeta, locality that Ptolemy places near the Tigris. Between the Hispanic form and the Anatolian one there is only a trivial difference: the vocalization of the intervocalic /t/ in the Hispanic form. On the other hand there are several parallels of the basic form Durba, from which Durbede / Durbeta has been derived by means of the suffix -ēto-. Finally the author proposes an etymology for the basic form Durba and diverse conclusions are obtained on the use of the above mentioned suffix.